Modelling and control of a reconfigurable multipurpose wheelchair for elderly/disabled mobility - Nor Maniha, Abdul Ghani (2015)
This research is embarking on development of modelling and designing control strategies for a multipurpose wheelchair as a mobile transporter for elderly and disabled people to move in confined and domestic environments independently. The research is aimed at helping people who have physical weakness/disabilities in their upper and lower extremities to move on their own without human intervention. In this work, a novel reconfiguration which allows multi-task operations using the same wheelchair system with compact and simple mechanism is developed for use in confined domestic environment. It can perform manoeuvrability on flat surfaces, stairs climbing (ascending and descending), standing in the upright position on two wheels and transforms back to standard four wheels with reduced initial torque and reduced tilt angle.